2015
DOI: 10.21829/azm.2015.3131044
|View full text |Cite
|
Sign up to set email alerts
|

Morfología del sistema reproductor de la hembra de Comadia redtenbacheri (Hammerschmidt) (Lepidoptera: Cossidae). Morphology of the female reproductive system of Comadia redtenbacheri (Hammerschmidt)

Abstract: RESUMEN. Debido a su importancia económica y con la finalidad de profundizar en el conocimiento sobre la biología reproductiva del  gusano rojo del maguey Comadia redtenbacheri (Hammerschmidt) (Lepidoptera: Cossidae), se determinó la morfología del sistema reproductor de la hembra de esta especie, el cual presenta en general las características básicas de otros Lepidoptera, con algunas particularidades  específicas. La fecundidad potencial tuvo un valor promedio de 104 ovocitos por hembra. En la base de la bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Also, in Zeuzera pyrina (L., 1761) (Lepidoptera: Cossidae), Durán et al (2004) observed that males have greater mobility than females, whose voluminous abdomens limit their movement. Also, Ramírez-Cruz & Llanderal-Cázares (2015) reported that the female C. redtenbacheri is proovigenic and emerges with 104 mature ovocytes ready to be fertilized and oviposited, limiting its flight capacity. This is the characteristic that could have reduced female arrival in the traps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in Zeuzera pyrina (L., 1761) (Lepidoptera: Cossidae), Durán et al (2004) observed that males have greater mobility than females, whose voluminous abdomens limit their movement. Also, Ramírez-Cruz & Llanderal-Cázares (2015) reported that the female C. redtenbacheri is proovigenic and emerges with 104 mature ovocytes ready to be fertilized and oviposited, limiting its flight capacity. This is the characteristic that could have reduced female arrival in the traps.…”
Section: Discussionmentioning
confidence: 99%
“…(Ancona, 1931;Brown, 1975;Ramos-Elorduy et al 2011). Information exists on its biology and behaviour (Miranda-Perkins et al 2013;Llanderal et al 2017), associated organisms parasitoids (Zetina et al 2009(Zetina et al , 2012Zetina & Llanderal, 2014) and bacteria (Hernández-Flores et al 2015), reproduction (Ramírez-Cruz & Llanderal-Cázares, 2015), morphology of all its developmental stages (Castro-Torres & Llanderal-Cázares, 2015, adult emergence in laboratory (Miranda-Perkins et al 2016), cultivation by induced infestation in agaves (Delgado-Tejeda et al 2017;Espinosa-García et al 2018), bionomics (Llanderal-Cázares et al 2017) and molecular delineation (Cárdenas-Aquino et al 2018). However, the biology, behaviour, and ecology of adults has not been studied, and the abiotic factors (temperature, relative humidity and rainfall) that affect its emergence are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The female lays the eggs in masses, and covers them with a brown secretion from the accessory glands, which are prominent and with a reservoir to store the secretion (Fig. 1b) (RAMÍREZ-CRUZ & LLANDERAL-CÁZARES, 2015). The secretion has a porous appearance under Scanning Electron Microscopy (Figs.…”
Section: Life Cycle and Ecologymentioning
confidence: 99%